Towards sustainable power generation with free piston engine generators: comparative analysis of hydrogen and methane fuels - Hadi Taghavifar; Dibyendu Roy; Kumar Vijayalakshmi Shivaprasad; Andrew Smallbone; Anthony Paul Roskilly (Fuel, 2026)

The impacts of the Ultra Low Emission Zone (ULEZ) and COVID-19 restrictions on air quality in central London – evidence for an increase in small particles - Douglas J. Gregg; Jordan Tompkins; Rebecca L. Cordell; Andrew S. Brown; Kirsty L. Smallbone; Joshua D. Vande Hey; Kevin P. Wyche; Paul S. Monks (Atmospheric Environment, 2026)

Impact of decarbonisation on water availability in the UK - Simon Mathias; Andrew Smallbone; Fred Worrall; Nigel Corfield; Tony March; Robert Barker (Sustainable Water Resources Management, 2025)
The UK aims to capture and store 20–30 Mt $$\hbox {CO}_{2}\hbox {e}$$ annually and produce 10 GW of low-carbon hydrogen by 2030. This study evaluates the potential water resource impacts of these decarbonisation efforts across five UK water company regions: Anglian Water, Northumbrian Water, Severn Trent Water, United Utilities, and Yorkshire Water. Projected $$\hbox {CO}_{2}$$ capture and hydrogen production rates are obtained from publicly available project databases and converted into associated water withdrawal rates using specific water intensity factors (SWIF) for $$\hbox {CO}_{2}$$ capture, blue hydrogen production and green hydrogen production. These SWIFs are derived through a combination of literature review and Integrated Environmental Control Model (IECM) simulations. Parameter uncertainty and project start-time uncertainty are incorporated using Monte Carlo simulation. Water withdrawals are spatially allocated to water company regions and compared with existing regional water availability forecasts derived from UK Water Resources Management Plans (WRMP24). Results indicate that additional water demand due to decarbonisation in the UK could reach 860 ± 150 ML/day by 2050, driven equally by $$\hbox {CO}_{2}$$ capture, blue hydrogen production, and green hydrogen production. Regional impacts vary, with significant deficits projected for Anglian Water and United Utilities by 2030 and for Yorkshire Water by 2040, while other regions are expected to maintain surplus capacity. Recommendations include adopting technologies with lower SWIF values, enhancing collaboration between decarbonisation project managers and water companies, establishing regional desalination hubs, redistributing water resources, and implementing adaptive water management strategies to ensure sustainable resource use.

Modelling of hydrogen blending into the UK natural gas network driven by a solid oxide fuel cell for electricity and district heating system - Samiran Samanta; Dibyendu Roy; Sumit Roy; Andrew Smallbone; Anthony Paul Roskilly (Fuel, 2024)

Life cycle assessment of microalgae-derived biodiesel - Tom Bradley; Mohammad Ali Rajaeifar; Andrew Kenny; Chris Hainsworth; Victória del Pino; Yago del Valle Inclán; Ines Povoa; Pedro Mendonça; Laura Brown; Andrew Smallbone; Anthony Paul Roskilly; Sharon Joyce; et al. (The International Journal of Life Cycle Assessment, 2023)
Purpose Microalgae-derived biofuels are considered a low-carbon alternative to fossil fuels. Nevertheless, as with all biofuels, there is still uncertainty around their sustainability. Most life cycle assessments (LCA) of microalgae biofuels so far used lab-based, scaled-up lab experimental data or data from the scientific literature. This article, provides evidence and analysis, undertaking an LCA using real-world data from an industrial facility that uses a combination of photobioreactor and fermenter systems. Methods The current well-to-wheel LCA study aimed to compare the environmental impacts of microalgae biodiesel production—under different energy regimes—and with petroleum-derived diesel. The functional unit was considered as “combustion of 1 MJ (Lower Heating Value) of algal biodiesel in an internal combustion engine (as B100)”. This LCA study considers the environmental and energy impacts from the construction of the facility, as well as those impacts from the operation of the facility. The foreground LCI data was collected from a real-world one-hectare microalgae production pilot facility. ReCiPe, IPCC AR5 (GWP100 and GWP20) and Global Temperature Potential (GTP) were implemented to assess the life cycle environmental impacts. Results and discussion The assessment shows that when infrastructure is included, microalgae-derived biofuels are not yet favourable over petroleum-derived fuels on GWP100, and this becomes worse over shorter timescales. In terms of climate change (GWP100), whilst 1 MJ (LHV) of fossil-derived diesel would emit 8.84 × 10 −2 kg CO 2 eq, 1 MJ of microalgae-derived biodiesel from a solar photovoltaic powered facility would emit 1.48 × 10 −1 kg CO 2 eq. To be equal to petroleum-derived diesel in terms of GWP100, or perform better, productivity of the microalgae production system needs to be improved as the most effective solution. The results also showed that electricity and infrastructure were major sources of environmental impacts, as well as the yeast used within the fermenter. Moreover, it takes 0.99 MJ of direct energy per 1 MJ of microalgae biofuel produced, similar to the fossil fuel industry for 1 MJ of diesel. Conclusions Using infrastructure and operational models, the study shows that the facility does not compare well with petroleum-derived diesel unless productivity can be increased. Productivity improvements, be it through improvements to microalgae strains or improved photobioreactor designs, should be a priority to ensure microalgae become a sustainable fuel feedstock. Electricity use should be reduced as well, again, through improved cultivation system designs. In terms of the current system, the high impacts of yeast should be addressed, either through co-locating yeast production or through ensuring specific sources with lower impacts. Extracting lipids will effectively waste some high-value products, whilst the waste can be expected to be a mixture of unextracted lipids, polysaccharides or fibre, some proteins and minerals. It is also shown that harmonisations of the assessments are needed for future studies and real-world operation facilities to conclusively decide if microalgae should be used as fuel or if they would be better used for other products, such as feed or high-value products.

Effect of ignition timing on the combustion process of a port injection free piston linear generator: A system level multi-physics coupling method - Zixuan Yang; Zhiyuan Zhang; Chang Liu; Huihua Feng; Boru Jia; Wei Wang; Andrew Smallbone; Tony Rosilly (Fuel, 2023)